PELATIHAN PERLINDUNGAN TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM DI DESA KUMELEMBUAI KABUPATEN MINAHASA SELATAN - Lesza Leonardo Lombok; Sam Julius Richard Saroinsong; Lega Ikhwan Herbayu (LPSDI Bina Patria, 2024)
Deprivation of a child's liberty is carried out as the last resort and for the minimum necessary period (in the shortest possible time). The main goal in child protection is to realize the best interests of the child. This service aims to provide training for parents, law enforcers and elements of society in handling children in conflict with the law and is carried out by giving lectures through training seminars. It is hoped that through the training seminars will solve the problems and lack of knowledge of the community in Kumelembuai Village in handling problems of children in conflict with the law can be resolved by prioritizing the best interests of the child